2020
DOI: 10.3389/fpsyt.2020.523059
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on Dynamics of Psychiatric Outpatients

Abstract: Background: Climate changes affect mental states and alter the risk for psychiatric diseases. Seasonal changes in temperature lead to dynamics in the occurrence of psychiatric conditions and pose challenges in the administration of clinical psychiatry services.Methods: The present study aims to retrospectively analyze outpatient data with weather reports from January 2014 to March 2019 at Shanghai Mental Health Center, one of the largest psychiatric hospitals in the world, in order to provide policy insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…Os impactos socioambientais na saúde mental, incluindo o suicídio, estão sendo cada vez mais estudados no contexto dos desafios globais relacionados às mudanças climáticas (XUE et al, 2019;QI;HU, 2009). Há evidências de que muitos distúrbios comportamentais e psiquiátricos, incluindo depressão maior e transtorno bipolar, estão relacionados a vários aspectos das condições ambientais e climáticas, como A G E \ mudanças na temperatura e quantidade de luz solar (ABBASI, 2021;SHAO et al, 2020).…”
Section: Transtornos Mentais E Comportamentaisunclassified
“…Os impactos socioambientais na saúde mental, incluindo o suicídio, estão sendo cada vez mais estudados no contexto dos desafios globais relacionados às mudanças climáticas (XUE et al, 2019;QI;HU, 2009). Há evidências de que muitos distúrbios comportamentais e psiquiátricos, incluindo depressão maior e transtorno bipolar, estão relacionados a vários aspectos das condições ambientais e climáticas, como A G E \ mudanças na temperatura e quantidade de luz solar (ABBASI, 2021;SHAO et al, 2020).…”
Section: Transtornos Mentais E Comportamentaisunclassified
“…Finally, additional attention should be paid to special populations, including psychiatric patient populations. Heat stress resulting in increased demand for acute psychiatric care may stress the already misaligned relationship between demand and need for psychiatric beds and thereby further strain the capacity of acute care facilities during an EHE (95,121). Health care systems should therefore establish preparedness frameworks accounting for special populations to ensure sustained health care service delivery.…”
Section: Tertiary Prevention and Event Activitiesmentioning
confidence: 99%
“…There is a positive association between specific meteorological factors and calls to emergency services, 3 emergency department visits 4,5 and hospital admission outcomes. 6,7 As regards the association between particular climatic factors and mental health, studies have demonstrated significant positive correlations with outpatients' visits for general psychiatric and psycho-consultation services, 8 evaluations in the psychiatric emergency department 9,10 and psychiatric hospital admissions. 11,12 Mental health involuntary admissions in Greece are regulated by Law 2071/1992.…”
Section: Introductionmentioning
confidence: 99%